E-Wallet Models: An Appraisal of Shariah Related Issues - Mohamed Naim, Asmadi; Iskandar Mirza, Azrul Azlan; A. Shukor, Abdul Rahman; Md. Nor, Mohd Zakhiri; Muhamed, Nurul Aini; Ahmad, Azuan; S. Ali, Shahrul Ridhwan (AHKAM : Jurnal Ilmu Syariah, 2023)
This paper aims to evaluate the existing e-wallet business models and to provide a preliminary analysis of Sharia issues, specifically related to the relationship of the involved parties in the contract (operators, customers, and third parties). As e-wallet is also a critical enabler to increase financial inclusion among the different levels of society members (richer and poor), thus there is an increasing need to analyze the existing e-wallet models and their practices. The final aims are to preserve all parties’ rights and support the policymakers to structure e-wallet parameters that comply with Islamic law. This paper adopts qualitative research approaches, specifically content analysis and interviews. The data collection includes, among others, document reviews, interviews, and observations. The paper evaluates four e-wallet models in Malaysia and analyzes arising Sharia issues from those models. In the models, several Sharia issues can be found, which are related to the contracts used, the status of funds held by e-wallet providers, deposits in banks, and revenue generation. Findings from this paper serve as a basis for scholars and policymakers to provide guidelines for Sharia-compliant e-wallets. Tulisan ini bertujuan untuk mengevaluasi model bisnis dompet elektronik yang ada dan memberikan analisis awal tentang masalah syariah, khususnya terkait dengan hubungan pihak-pihak yang terlibat dalam kontrak (operator, pelanggan dan pihak ketiga). Karena dompet elektronik juga merupakan faktor penting untuk meningkatkan inklusi keuangan di antara berbagai tingkat anggota masyarakat (kaya dan miskin), maka ada peningkatan kebutuhan untuk menganalisis model dompet elektronik yang ada dan praktiknya. Tujuan akhirnya adalah untuk menjaga hak semua pihak dan mendukung pembuat kebijakan untuk menyusun parameter dompet elektronik yang sesuai dengan hukum Islam. Tulisan ini mengadopsi pendekatan penelitian kualitatif, khususnya analisis isi dan wawancara. Pengumpulan data meliputi telaah dokumen, wawancara, dan observasi. Tulisan ini mengevaluasi empat model dompet elektronik di Malaysia dan menganalisis masalah syariah yang muncul dari model tersebut. Ada beberapa masalah syariah yang dapat ditemukan dari model-model tersebut, yaitu terkait dengan akad yang digunakan, status dana yang dipegang oleh penyedia dompet elektronik, status simpanan di bank dan perolehan pendapatan. Temuan dari makalah ini dapat digunakan sebagai dasar bagi para sarjana dan pembuat kebijakan untuk memberikan pedoman dompet elektronik yang sesuai syariah.